2007
DOI: 10.1039/b704372d
|View full text |Cite
|
Sign up to set email alerts
|

Pentafluorophenyl copper: aggregation and complexation phenomena, photoluminescence properties, and applications as reagent in organometallic synthesis

Abstract: Recent advances in the chemistry of pentafluorophenyl copper are discussed, including the observation of strongly luminescent adducts with pyridine, the first successful structural characterization of an organocopper-arene complex, and the complexation with electron-rich transition metal complexes such as ferrocene derivatives. In addition, new applications in synthetic organometallic chemistry are discussed, which include the discovery of tin/copper exchange reactions for the preparation of organocopper compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 96 publications
2
26
0
Order By: Relevance
“…In earlier work we found that (C 6 F 5 Cu) 4 and (MesCu) n (Mes = 2,4,6-trimethylphenyl; n = 4, 5) can serve as mild reagents for the transfer of aryl groups to boron [3,8]. In fact, the reagent (C 6 F 5 Cu) 4 has been successfully employed in areas ranging from molecular Lewis acid chemistry [9,10] to polymeric Lewis acids [11], conjugated materials [12], and even amphiphilic borate block copolymers [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier work we found that (C 6 F 5 Cu) 4 and (MesCu) n (Mes = 2,4,6-trimethylphenyl; n = 4, 5) can serve as mild reagents for the transfer of aryl groups to boron [3,8]. In fact, the reagent (C 6 F 5 Cu) 4 has been successfully employed in areas ranging from molecular Lewis acid chemistry [9,10] to polymeric Lewis acids [11], conjugated materials [12], and even amphiphilic borate block copolymers [13].…”
Section: Resultsmentioning
confidence: 99%
“…Pentafluorophenyl copper, which was first introduced by Cairncross and Sheppard more than 40 years ago [1], exists as a tetrameric aggregate in the solid state, which is also believed to be the predominant species in solution [2,3]. A variety of structurally intriguing complexes with Lewis bases have been reported also and, in recent years, the electron-deficient character of pentafluorophenyl copper has been exploited in the assembly of luminescent supramolecular structures [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Copper(II) complexes continue to receive attention [1] because of chemical, biological and industrial importance. Inorganic chemistry of copper(II) is fascinating owing to: (i) copper(II) exhibits a variety of coordination number (4)(5)(6)(7)(8) with associated geometries (ii) copper(II) complexes are liable to Jahn-Teller distortion, (iii) the anionic ligand may be non coordinated or coordinated, (iv) it is one of constituent metal ions in most of superconductors and (v) the copper(II) compounds for (e.g. carboxylates) may be monomeric, dimeric or polymeric.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial applications of copper salts include electroplating, as catalysts (copper(II)triflate), as insecticide, ink and paints (cupric phthalocyaninate), cupric b-diketonates as precursor for deposition of thin films of copper by chemical vapour deposition, reagent in organic synthesis etc. [5]. Cu (hexafluoroacetylacetonate) 2 is widely used in synthesis of molecular magnets [6].…”
Section: Introductionmentioning
confidence: 99%
“…97 Meanwhile, in a structural vein, the aggregation and complexation behaviour of pentafluorophenyl copper has been discussed, along with its applicability to photochemistry and organometallic synthesis. 98 a-Halonitriles have been converted into reactive metallated nitriles using alkyllithium, organomagnesium, and lithium dimethylcuprate substrates. Subsequent reactivity varies, with lithiated and magnesiated nitriles reacting with propargyl bromide by S N 2 displacement but with C-metallated organocopper nitriles evidently converting through an S N 2 0 route.…”
Section: Coppermentioning
confidence: 99%